Defining Feedback: Understanding Students' Perceptions of Feedback in the Introductory Communication Course - Drew T. Ashby-King; Raphael Mazzone; Lindsey B. Anderson (Central States Communication Association, 2021)
Feedback is an essential part of the teaching/learning processes. This statement is especially true in the introductory communication course where students receive feedback throughout the presentational speaking process. This paper explores how students define useful feedback based on 1,600 qualitative questionnaires that asked students about their perceptions of feedback. A thematic analysis of a randomly selected subset of 163 responses uncovered two themes: (1) feedback content characteristics (e.g., specific, constructive, praiseworthy, and purposive) and (2) process of instructor-provided feedback (e.g., iterative, timely). Based on these findings, a set of best practices for providing feedback is offered as a means to improve teaching/learning in the introductory communication course.